2018
DOI: 10.3390/sym10100442
|View full text |Cite
|
Sign up to set email alerts
|

Facial Feature Model for a Portrait Video Stylization

Abstract: With the advent of the deep learning method, portrait video stylization has become more popular. In this paper, we present a robust method for automatically stylizing portrait videos that contain small human faces. By extending the Mask Regions with Convolutional Neural Network features (R-CNN) with a CNN branch which detects the contour landmarks of the face, we divided the input frame into three regions: the region of facial features, the region of the inner face surrounded by 36 face contour landmarks, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Berger et al [3] proposed a data-driven approach to learn the portrait sketching style, by analyzing strokes and geometric shapes in a collection of artists' sketch data. Liang et al [19] proposed a method for portrait video stylization by generating a facial feature model using extended Mask R-CNN and applying two stroke rendering methods on sub-regions. The above methods generate results of a specific type of art, e.g., curved brush stroke portrait, portrait sketching.…”
Section: Non-photorealistic Rendering Of Portraitsmentioning
confidence: 99%
“…Berger et al [3] proposed a data-driven approach to learn the portrait sketching style, by analyzing strokes and geometric shapes in a collection of artists' sketch data. Liang et al [19] proposed a method for portrait video stylization by generating a facial feature model using extended Mask R-CNN and applying two stroke rendering methods on sub-regions. The above methods generate results of a specific type of art, e.g., curved brush stroke portrait, portrait sketching.…”
Section: Non-photorealistic Rendering Of Portraitsmentioning
confidence: 99%
“…The main idea of Mask RCNN is to locate multiple feature regions in an image, input each region into CNN for feature extraction [16] and generate a Mask on the feature-extracted region. The biggest feature of Mask RCNN is to separately extract the classified regression information of the image to be tested (that is, the border information of the target to be tested) and combine it with the pyramid features (the length and width of the image input for pyramid region of interest [ROI] processing, that is, PyramidROIAlign) for mask generation, which is shown in Figure 1.…”
Section: Related Workmentioning
confidence: 99%
“…Many relevant research studies have been reported and many algorithms have been proposed that achieve a satisfactory visual effect [29]- [34]. In [32], Liang et al proposed a method for automatically stylizing portrait videos that contain small human faces that extends the mask regions with the convolutional neural network (R-CNN) features. The experimental results demonstrated that the method could effectively preserve the small and distinct facial features.…”
Section: Related Workmentioning
confidence: 99%